Infestation of Bemisia tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) and Caliothrips phaseoli (Hood.) (Thysanoptera: Thripidae) in beans genotypes. - Jesus, F.G.; Boica Junior, A.L.; Carbonel, S.A.M.; Stein, C.P.; Pitta, R.M. (My University, 2009)
The objective of this work was to evaluated the infestion of the whitefly Bemisia tabaci (Genn.) B biotype and thrips Caliothrips phaseoli (Hood) in fifteen beans genotypes in field condition. The genotypes IAPAR 31, Rosinha G2, Jalo precoce, Perola, IAC Harmonia, Gen 99TGR110, Gen 99TG2868, Gen 99TGR3416, Gen 99TG3450, Gen 99TG823, Gen 99TGR609, IAC Jaragua, Gen 95A10061531, Gen 99TGR3114 e Gen 96A1473153V2 was used. The experiment was conducted from May to July 2006. The statistical design was randomized blocks, totalizing 15 treatments and four replications. Evaluation was realized weekly, totalizing seven samplings. The evaluations were accomplished on a weekly basis by counting B. tabaci biotype B eggs and nymphs and nymphs of C. phaseoli in 10 leaflets per plot. The less oviposition genotypes by B. tabaci biotype B were IAC Harmonia, Perola, Gen TG3114 e Gen 95A10061531, while the most oviposited were IAC Jaragua and Gen 99TG3450. The less presence of nymphs of whitefly were observed on Perola and IAC Harmonia and the most at IAC Jaragua. It was observed a negative and non significant linear correlation between average temperature versus number of silverleaf whitefly and temperature versus number of thrips was verified.